Using Anterior Segment Optical Coherence Tomography to Monitor Disease Progression in Peripheral Ulcerative Keratitis. (28th June 2018) - Garg, Aakriti; De Rojas, Joaquin; Mathews, Priya; Hazan, Albert; Lin, James; Trief, Danielle; Suh, Leejee H.
Abstract : We report two cases of peripheral ulcerative keratitis (PUK) imaged with anterior segment optical coherence tomography (AS-OCT). The first patient had prolonged nonsteroidal anti-inflammatory drug use, while the second had inflammatory arthritis by laboratory findings without any systemic findings as well as possible concurrent tuberculosis. In both patients, AS-OCT demonstrated corneal thinning at the onset of the disease with improvement six months after initiation of intensive medical therapy. Our cases highlight the need for a multidisciplinary approach and careful monitoring in PUK cases, especially with objective measures such as corneal thickness assessed with AS-OCT.